KEMAMPUAN GURU SD DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR KREATIF PADA PELAJARAN IPA - Yuli Nurul Fauziah (Jurnal Pendidikan, 2010)
This study aims to analyze the ability of elementary school teacher to develop creative thinking skills in teaching science. The research was conducted at grade 5 of 11 elementary schools in the city of Bandung during the 2010-2011 school year. Research subjects were 5 certified teachers through portfolio program, 5 certified teachers through training program, and 5 uncertified teachers. Data collection include analyzing lesson plans, observing learning processes, recording the process of learning through vidoegraph and conducting evaluation tests. Data were analyzed based on the characteristics of creative thinking; which were fluency, flexibility, originality and elaborateness. Results revealed that elementary school teacher had drawn up plans to develop creative thinking skills in their lesson plans, but still could not implemented them in learning activities in classroom. It was concluded that the development of creative thinking skills in science teaching had not been executed effectively. It is suggested that teachers should be encouraged to carry out the learning process that is able to develop creative thinking skills.